2011
DOI: 10.1007/s00221-011-2569-3
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic membrane properties of central vestibular neurons in rodents

Abstract: Numerous studies in rodents have shown that the functional efficacy of several neurotransmitter receptors and the intrinsic membrane excitability of central vestibular neurons, as well as the organization of synaptic connections within and between vestibular nuclei can be modified during postnatal development, after a lesion of peripheral vestibular organs or in vestibular-deficient mutant animals. This review mainly focuses on the intrinsic membrane properties of neurons of the medial vestibular nuclei of rod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 86 publications
1
17
0
Order By: Relevance
“…These results from in vitro studies (59) and from frogs (6066) have been shown to apply also in mammalian vestibular system. Type A and B neurons previously found in brainstem slices were identified in the guinea pig whole-brain preparation, and these neurons receive direct inputs from the vestibular nerve.…”
Section: Physiological Datamentioning
confidence: 62%
“…These results from in vitro studies (59) and from frogs (6066) have been shown to apply also in mammalian vestibular system. Type A and B neurons previously found in brainstem slices were identified in the guinea pig whole-brain preparation, and these neurons receive direct inputs from the vestibular nerve.…”
Section: Physiological Datamentioning
confidence: 62%
“…However, VVM neurons showed a decrease of their spontaneous firing rate in comparison to control neurons (Mann–Whitney test, z = –2.49, p = 0.013) and a slightly more regular spontaneous discharge than control neurons (CV of 0.16 vs. 0.22; Mann–Whitney test, z = 1.97, p = 0.048). MVN neurons were previously shown to be composed of different subpopulations that can be partly segregated using their electrophysiological signature at rest (Straka et al, 2005; Eugène et al, 2011; Beraneck and Idoux, 2012). Hence, we further divided the recorded neurons using the canonical type A and type B classification.…”
Section: Resultsmentioning
confidence: 99%
“…At this age, glutamate receptor-mediated postsynaptic responses within the VN also reach a status that is comparable to that observed at P21, suggesting that effective transmission of head rotational input is achieved within the first postnatal week (cf. Eugène et al 2011). It is noteworthy that appearance of head-turning response (cephalic response) also occurs at P4 in rats (Parrad and Cottereau 1977).…”
Section: Sequential Maturation Of the Vestibulo-olivary Pathwaymentioning
confidence: 98%